Effects of personalized 3D-printed blocks in total knee arthroplasty and revision surgery for massive bone defects: a single-center retrospective study - Fei Lu; Congsun Li; Pengfei Hu; Bin Hu; Haobo Wu (Journal of International Medical Research)
Objective To analyze the early- to mid-term clinical efficacy of personalized 3D-printed structural metal spacer technology in reconstructing massive bone defects during complex total knee arthroplasty (TKA) and revision surgery. Methods A single-center retrospective study was conducted on nine patients with severe bone defects who underwent TKA between 2018 and 2024. The general condition, surgical details, and clinical improvement of these patients were recorded and analyzed by clinical doctors. Results The average surgical duration was 183.9 minutes (range, 125–240 minutes), with intraoperative blood loss of 133.3 mL (range, 100–200 mL). The average hospital stay was 18.2 days (range, 10–42 days), and the follow-up duration was 13.2 months (range, 2–57 months). The preoperative average American Knee Society Score of 51.2 points (range, 15–74 points) improved significantly to 95.0 points (range, 81–106 points) at the last follow-up. No cases of vascular or nerve injury, infection, fracture, or prosthetic loosening were observed. Conclusion The precise manufacturing of customized spacers that seamlessly integrate with the patient’s skeletal structure ensures stability, adaptability, and improved surgical outcomes.